Recognition of musical beat and style and applications in interactive humanoid robot - Chu, Yue (Frontiers in Neurorobotics, 2022)
The musical beat and style recognition have high application value in music information retrieval. However, the traditional methods mostly use Convolutional Neural Network (CNN) as the backbone and have poor performance. Accordingly, the present work chooses a Recurrent Neural Network (RNN) in Deep Learning (DL) to identify musical beats and styles. The proposed model is applied to an interactive humanoid robot. Firstly, DL-based musical beat and style recognition technologies are studied. On this basis, a note beat recognition method combining Attention Mechanism (AM) and independent RNN (IndRNN) [AM-IndRNN] is proposed. The AM-IndRNN can effectively avoid gradient vanishing and gradient exploding. Secondly, the audio music files are divided into multiple styles using the music signal's temporal features. A human dancing robot using a multimodal drive is constructed. Finally, the proposed method is tested. The results show that the proposed AM-IndRNN outperforms multiple parallel Long Short-Term Memory (LSTM) models and IndRNN in recognition accuracy (88.9%) and loss rate (0.0748). Therefore, the AM-optimized LSTM model has gained a higher recognition accuracy. The research results provide specific ideas for applying DL technology in musical beat and style recognition.